Intravenous Thrombolytic Treatment in the Oldest Old - Juan García-Caldentey; María Alonso de Leciñana; Patricia Simal; Blanca Fuentes; Gemma Reig; Fernando Díaz-Otero; Marta Guillán; Ana García; Patricia Martínez; Andrés García-Pastor; José Antonio Egido; Exuperio Díez-Tejedor; et al. (Stroke Research and Treatment)
Background and Purpose. Intravenous thrombolysis using tissue plasminogen activator is safe and probably effective in patients >80 years old. Nevertheless, its safety has not been specifically addressed for the oldest old patients (≥85 years old, OO). We assessed the safety and effectiveness of thrombolysis in this group of age. Methods. A prospective registry of patients treated with intravenous thrombolysis. Patients were divided in two groups (<85 years and the OO). Demographic data, stroke aetiology and baseline National Institute Health Stroke Scale (NIHSS) score were recorded. The primary outcome measures were the percentage of symptomatic intracranial haemorrhage (SICH) and functional outcome at 3 months (modified Rankin Scale, mRS). Results. A total of 1,505 patients were registered. 106 patients were OO [median 88, range 85–101]. Female sex, hypertension, elevated blood pressure at admission, cardioembolic strokes and higher basal NIHSS score were more frequent in the OO. SICH transformation rates were similar (3.1% versus 3.7%, P=1.00). The probability of independence at 3 months (mRS 0–2) was lower in the OO (40.2% versus 58.7%, P=0.001) but not after adjustment for confounding factors (adjusted OR, 0.82; 95% CI, 0.50 to 1.37; P=0.455). Three-month mortality was higher in the OO (28.0% versus 11.5%, P<0.001). Conclusion. Intravenous thrombolysis for stroke in OO patients did not increase the risk of SICH although mortality was higher in this group.